Anti-tumor effect of ribavirin in combination with interferon-α on renal cell carcinoma cell lines in vitro - Teng, Lichen (Cancer Cell Int, 2014)
BACKGROUND: Ribavirin is an anti-viral drug; however, recent data suggest that it may also be effective in cancer therapy. This study investigated the effect of ribavirin alone or in combination with IFN-α on biological processes: proliferation, apoptosis, and migration of murine (Renca) and human renal carcinoma (RCC) cells (786–0) in vitro. METHODS: Renca and 786–0 cells were treated with IFN-α, ribavirin, or a combination of IFN-α and ribavirin at varying concentrations. Cell proliferation was evaluated using CCK-8 assay. Induction of apoptosis and distribution of cell cycle were determined by flow cytometry. The migratory capacity of cells was quantified using a transwell migration assay. The toxic effect of these drugs was examined using MTT assay in HEK-293 cells. ELISA was used to measure IL-10 and TGF-β content in the culture supernatants. RESULTS: Our results showed that both ribavirin alone and in combination with IFN-α could significantly inhibit the cell proliferation and arrest the cell cycle progress at the G2/M phase. These treatments also inhibited cell migration and IL-10 production, in a concentration-dependent manner, in 786–0 and Renca cells. Moreover, they significantly induced apoptosis of RCC cells and increased TGF-β production in concentration-dependent manner. No significant toxic effect was observed in HEK-293 cells. We also found that the effect of combined treatment was more pronounced than that of ribavirin or IFN-α alone. However, the combined effect of the two drugs was not synergistic. CONCLUSION: Our findings suggest that ribavirin can negatively affect biological processes of RCC cells. This agent might become a new candidate for the treatment of RCC in the clinical setting.